STUDI KELAYAKAN USAHA DAN DAYA SAING PADA INDUSTRI TEPUNG TAPIOKA DI KECAMATAN POGALAN KABUPATEN TRENGGALEK - Winda Amilia; Miftahul Choiron (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2017)
Small and Medium Enterprises play an important role for economic growth in Indonesia. As an agricultural country, development on agricultural sector should be done to meet the needs of industries. As agricultural commodities, cassava requires processing efforts to increase the product value. Anis Jaya has been processing tapioca flour since 1983 in the center of tapioca flour on Pogalan, Trenggalek Regency. Since 2015, Anis Jaya has decreased production number, due to the decline on market demand. This has an impact on the decline of cassava purchasing price by industry. Therefore, the objective of this research is to analyze the feasibility of Anis Jaya business and to analyze business competitiveness using Porter’s Diamond model approach for business development. The analysis shows that the Net Present Value is Rp. 88.690.571,74 (NPV > 1), Internal Rate of Return is 54,98% and Payback Period less than 1 year. Net B/C ratio of Anis Jaya is 2,82 which indicates that the industry is still worth continuing. The formulated development strategy is making efficiency by adding capital, improving product and service quality, optimizing labor performance, and managing raw material inventory and auxiliary materials.